2020
DOI: 10.2308/jiar-19-514
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Equity Ownership and Income Smoothing

Abstract: We examine whether foreign investors influence a local firm's income smoothing, using a sample of Korean firms from 2000 to 2013. We hypothesize that given innate informational difficulties of overseas investments, foreign investors demand less noisy and more sustainable earnings, and to satisfy this demand, managers have strong incentives to smooth earnings. We find that foreign investors' ownership is positively related to the level of earnings smoothing. We also find that earnings smoothing improves earning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
1
4
2
1
Order By: Relevance
“…More so, this suggests that smoothen practices are seen to signal private information by managers to investors, thus, income smoothing is perceived from the information view rather than the garbling (managerial opportunistic) view. This result supports the findings of Allayannis and Simko (2009), Bitner and Dolan (1996), Habib et al (2011), De Jong et al (2013), Jung et al, (2020, Makela (2012), Takasu and Nakano (2012), and Yang and Zhu (2014) that found smoothing of earnings improves the informativeness of earnings and signal future earnings persistence to investors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…More so, this suggests that smoothen practices are seen to signal private information by managers to investors, thus, income smoothing is perceived from the information view rather than the garbling (managerial opportunistic) view. This result supports the findings of Allayannis and Simko (2009), Bitner and Dolan (1996), Habib et al (2011), De Jong et al (2013), Jung et al, (2020, Makela (2012), Takasu and Nakano (2012), and Yang and Zhu (2014) that found smoothing of earnings improves the informativeness of earnings and signal future earnings persistence to investors.…”
Section: Discussionsupporting
confidence: 89%
“…The result of the interaction of the variables arose from findings of previous studies on how environmental uncertainty might motivate income smoothing practice or behavior. In high market volatility, investors' prefer stable earnings as this gives assurance to investors on the financial position of the firms (Chen et al, 2020;Cvetanovska and Kerekes, 2015;Habib et al, 2011;Jung et al, 2020;Takasu and Nakano, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, the information environment in GCC is categorized as less informative, so foreign investors encounter difficulties when trying to understand whether the earnings smoothness practices improve earnings informativeness. This result is not in line with Jung et al (2020) which found that foreign investors demand earnings smoothness to improve the earnings informativeness in Korea.…”
Section: Contemporary Management Research 259contrasting
confidence: 73%
“…The result of this measure is not in line with Jung et al (2020) which found a positive association between FI and income smoothing as foreign investors demand more sustainable earnings, and this can be done by earnings smoothness. This result is also not in line with Rountree et al (2008) which found that investors evaluate earnings smoothness negatively.…”
Section: Measuring and Analysis Of Eq-sm And Ficontrasting
confidence: 63%